The ear from nowhere: Listening techniques and the politics of negation in the practice of Japanese interfaith chaplains. (March 2020) - Berman, Michael
Abstract: This article examines the politics of listening in the work of Japanese interfaith chaplains. It argues that listening is an important but often overlooked aspect of language ideologies and, more specifically, of the formation of modern subjects. Interfaith chaplains are religious professionals who apply principles of clinical psychology to help people in settings ranging from hospices to disaster areas. The desire to help suffering people who do not share the same religious backgrounds as the chaplains motivates them to cultivate what I call an "ear from nowhere, " which is divorced from their respective religious traditions and from speaking-based authority. Highlights: Japanese interfaith chaplains make themselves felt without resorting to speaking. Working to listen rather than offer salvation created tension in chaplains' practice. Speaking during a session was construed as an attempt to control conversation. Listening can count as a means to provide justice without a redistribution of power. The burden of listening can fall on people from non-hegemonic semiotic traditions.